Galectin-1 Inhibition as a Strategy for Malignant Peripheral Nerve Sheath Tumor Treatment - Hsiao-Chi Wang; Keila E. Torres; Roger Xia; Marcio H. Malogolowkin; Ssu-Wei Hsu; Ching-Hsien Chen; Tsung-Chieh Shih (Cells)
Neurofibromatosis type 1 (NF1) is an inherited disorder that predisposes individuals to malignant peripheral nerve sheath tumors (MPNSTs), a highly aggressive sarcoma with limited treatment options and poor prognosis. This study explores the potential of targeting the interaction between Galectin-1 and Ras as a novel therapeutic strategy for MPNSTs. Through molecular docking, we identified critical residues involved in the Galectin-1 and H-Ras interaction. We developed LLS30, a compound designed to target this Ras-binding pocket on Galectin-1, and tested its efficacy. LLS30 effectively disrupted the Galectin-1/Ras interaction, causing Ras delocalization from the plasma membrane and inhibiting Ras signaling. In vitro experiments showed that LLS30 significantly decreased MPNST cell proliferation and induced apoptosis. In vivo, LLS30 demonstrated potent anti-tumor effects, reducing tumor size, inhibiting metastasis, and extending survival in animal models. Transcriptome analysis further revealed the downregulation of KRAS signaling and inhibition of pathways associated with epithelial–mesenchymal transition. These findings suggest that targeting Galectin-1 with LLS30 offers therapeutic potential for MPNSTs and could be beneficial for other cancers driven by Galectin-1 and Ras signaling.